THE VIEW OF BRAZILIAN MILITARY FIRE DEPARTMENTS TOWARDS THEIR MEMBERS EMPLOYED IN DISASTER RESPONSE - Flores, Bráulio Cançado; Najberg, Estela (Seven Editora, 2025)
The relationship between public safety and human rights is not limited to the services that institutions and their members provide to society. Beyond the discussion of the service provided, it is also necessary to recognize that public safety operators are also subjects of rights. These individuals are often exposed to severe scenarios, such as disaster response. Among public safety professionals, the most frequent disaster responders are firefighters. Aiming to understand the designation of firefighters who respond to disasters from the perspective of their institutions and the care they provide to their personnel, this study collected information from all military fire departments (CBMs) in Brazil through questionnaires. These questionnaires revealed that institutions are highly committed to their mission, that prepare and employ their agents to fulfill their duty, but that they still find room for improvement in recognizing these individuals as human beings who will invariably be impacted by their exposure to scenarios complexly impacted by disasters. DOI: https://doi.org/10.56238/sevened2025.029-030